PENTINGNYA PENDIDIKAN KARAKTER PADA ANAK SEKOLAH DASAR DI ERA DIGITAL - Muhammad Sheva Sofbriaz Ashari; Desty Endrawati Subroto; Nurdiansyah Dwi Saptian (Sindoro: Cendikia Pendidikan, 2025)
Character education for elementary school children in the digital era is crucial for shaping a generation that is not only intellectually capable but also morally upright. This study discusses the importance of character education amid the rapid development of technology, as well as the positive and negative impacts of technology on children's character. Technology provides children with faster access to information, but without proper supervision, they may fall into negative behaviors such as digital addiction, the spread of misinformation, and cyberbullying. This study suggests the significant role of educators, parents, and society in guiding children to use technology wisely and responsibly. With an integrated educational approach, children can be equipped with strong character and the ability to face challenges in the digital world with good morals. The study recommends integrating character education into the use of technology and emphasizes the importance of adequate supervision in guiding children to be not only smart but also morally responsible in their use of technology.